Podcast use motivations and patterns among college students - Chung, Mun-Young (Kansas State University, 2008)
Despite its increasing use and potential benefits for college education, podcasts have been little studied in the literature of the use and gratifications theory. To explore podcasts use among college students, this study investigated their motivations to use and their use behavior/attitude with respect to the medium. Based on a survey sample of 636 college students at a Midwestern university, this study found that students may have six motivations for podcasts: 1) Voyeurism/Social interaction/Companionship, 2) Entertainment/Relaxation/Arousal, 3) Education/Information, 4) Pastime/Escape, 5) Habit, and 6) Convenience. Of the six identified motivations, Education/Information clearly showed that podcasts have become widely used among students as an appealing medium for their school work. Moreover, as similar as the cellular phone study, this study identified a Fashion motivation for podcasts use. Lastly, this study found and discussed noticeable differences and similarities between podcasts and television regarding users' motivations, the interrelationships among motivations, and the predictive relationships between motivations and use behavior/attitude.
Keywords: Podcasts; College students; Uses and gratifications; Motivation; Behavior; Attitude; Education, Technology (0710); Mass Communications (0708)